2019
DOI: 10.17759/cpp.2019270204
|View full text |Cite
|
Sign up to set email alerts
|

Professional Burnout and Reflection of Professionals Helping Professions

Abstract: Тhis paper attempts to address the relationship of reflection, supervision, and professional burnout of psychologists and psychotherapists. The sample of the pilot study included 38 people, including 27 women and 11 men. Тhe average age of the subjects was 36.6 years for women (range: 24—55) and 39.1 years for men (range: 29—57). The following methods were used: Burnout Inventory (Maslach, Jackson, 1981; Vodop’yanova, Starchenkova, 2005); Differential Diagnostics of Reflexivity (Leont’ev, Lapteva, Osin, Salikh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The “professional supervision,” seen as necessary by some social workers, as a moment of reflection and professional and emotional support, is perceived as a “challenge” as it is not present in all services. However, the supervision tool would allow to address some of the critical issues (Matyushkina, 2019; Rae et al, 2017) highlighted by social workers such as “overwork,” “lack of competence,” and a “sense of abandonment,” which in the literature are considered factors that can lead to work burnout (George-Levi et al, 2020; Joaquim et al, 2018). Indeed, according to Robinson (2013), the professional supervision function, due to the ethically demanding nature of the work and the impact on the health of social workers, improves support for those who work in particular with asylum seekers and refugees.…”
Section: Discussionmentioning
confidence: 99%
“…The “professional supervision,” seen as necessary by some social workers, as a moment of reflection and professional and emotional support, is perceived as a “challenge” as it is not present in all services. However, the supervision tool would allow to address some of the critical issues (Matyushkina, 2019; Rae et al, 2017) highlighted by social workers such as “overwork,” “lack of competence,” and a “sense of abandonment,” which in the literature are considered factors that can lead to work burnout (George-Levi et al, 2020; Joaquim et al, 2018). Indeed, according to Robinson (2013), the professional supervision function, due to the ethically demanding nature of the work and the impact on the health of social workers, improves support for those who work in particular with asylum seekers and refugees.…”
Section: Discussionmentioning
confidence: 99%
“…Матюшкиной и А.А. Кантемировой, которые указывают на то, что перестройка рефлексивных процессов в процессе прохождения супервизии и интервизии препятствует развитию профессионального выгорания у специалистов помогающих профессий [12].…”
Section: For Citationunclassified
“…Although it is not easy to prove the link between reflection, educators' well-being, and the efficacy of interventions to promote team reflexivity, multiple studies have suggested that reflexive practices improve relationships with others and with one's professional practice. It thus protects from the risk of burnout, especially in unpredictable and complex environments (Widmer et al, 2009;Morgan et al, 2013;Matyushkina and Kntemirova, 2019).…”
Section: Introduction Professional Self Well-being and Teamsmentioning
confidence: 99%